The Research on Sports Risk Management and Strategy in Higher Vocational Colleges in China: A Case Study of Guizhou in China - Yuhan , Liu; Cheng-Te Lin, (Journal of Roi Kaensarn Academi, 2024)
In recent years, China's rapid economic and social development has led to significant expansion in vocational education, including school sports programs in vocational colleges. However, this growth has been accompanied by an increase in school sports injury accidents, raising societal concerns and potentially impeding the development of higher vocational sports. This study aims to investigate the safety risks associated with school sports in Chinese higher vocational colleges, utilizing risk management knowledge systems to analyze and provide recommendations for mitigating these risks. The research employs a theoretical analysis approach, exploring basic concepts of risk management, including risk connotation and risk management content. It analyzes the entire risk management process, with a particular focus on the procedures and methods of risk identification and risk assessment in the context of higher vocational school sports. The study identifies key safety risks in higher vocational school sports and outlines the process of risk management applicable to this context. Based on this analysis, the study offers decision-making recommendations for managing and mitigating safety risks in higher vocational school sports. These findings contribute to the development of more effective risk management strategies in vocational education sports programs, potentially reducing accidents and promoting safer sporting environments in Chinese higher vocational colleges.